The Influence Of Sales Funnel Marketing On Brand Awareness Through Social Media Influencers - Wiraguna, Rayie Tariaranie; Dini Aulia (ADPEBI Publisher, 2024)
Purpose – This research aims to examine more deeply how sales funnel marketing can influence brand awareness trough social media influencers and develop marketing management knowledge on this topic.. Methodology/approach –The method used in this research is a quantitative method with path analysis using the Smart PLS 4 application. The data measurement technique in this study uses a likert scale range from strongly agree 5 to strongly disagree 1. The subject of this research are followers of the @erigostore Instagram account as many as 132 respondent male or female with age 18-45 years. Findings –The result showed that the use of sales funnel marketing in increasing brand awareness had a moderate effect as the structural level (f-square = 0.197). The use of influencers is able to marketing on brand awareness with a path coefficient (0.264) and o-value (0.000 < 0.05). as the structural level, the mediating role of influencers is classified as a moderate mediating effect (upsilon-v = 0.75). Novelty/value – There are still few previous studies that directly connect these 3 variables by adding influencers. In isnaini et al (2022) it is explained that sales funnel marketing has an effect on increasing brand awareness, but a lead magnet or bait is needed. Previous research was studied in companies engaged in services, while this research is in the fashion industry.